Testing the Reference of Biological Kind Terms. Issue 5 (21st May 2021) - Devitt, Michael; Porter, Brian C.
Abstract: Recent experimental work on "natural" kind terms has shown evidence of both descriptive and nondescriptive reference determination. This has led some to propose ambiguity or hybrid theories, as opposed to traditional description and causal‐historical theories of reference. Many of those experiments tested theories against referential intuitions. We reject this method, urging that reference should be tested against usage, preferably by elicited production. Our tests of the usage of a biological kind term confirm that there are indeed both descriptive and causal‐historical elements to the reference determination of some natural kind terms. We argue that to accommodate our results and earlier ones, we should abandon the common assumption that any one theory of reference fits all natural kind terms. Rather, it is likely that some terms are descriptive, some causal‐historical, some ambiguous, and some hybrid. This substantive conclusion is accompanied by a methodological one. Our experiments, like some earlier ones, found participants contradicting both each other and themselves. We argue that these contradictions indicate a lack of linguistic competence with the term. We conclude that these experiments have been faulty, because they test terms that are novel to participants and/or use fantastical vignettes. We provide some suggestions for future research.